Concepções de empreender e o desenvolvimento da competência empreendedora: um estudo à luz da fenomenografia - Amaro, Rubens de Araújo (2012)
The central objective of this study is to analyze how different conceptions of enterprise influence the development of the enterprising competency, taking as a reference the phenomenographic assumption that a single phenomenon is experienced in different ways by individuals. Generally, studies in this field treat competency as a set of attributes held by individuals and activated in real situations to resolve problems and take opportunities. They are based on a realist ontology, where subject and object are considered separate entities, and on an objectist epistemology, which presupposes that there is an objective meaning to all dimensions of the social world, waiting to be discovered by researchers. As a result, a set of individuals attributes that are independent of context are identified. These studies do not take into consideration the influence of the meanings that individuals attribute to their activities when developing their competency for enterprising. This gap is filled by this research, which is based on the idea that the different conceptions entrepreneurs have of their activities both form and organize the attributes put into play when these activities are performed. For this purpose, qualitative research using a methodology that is little known in organizational studies, phenomenography, was conducted. The main authors of this investigation approach are Ference Marton, Roger Säljö and John Bowden in the education area, and Gloria Dall Alba and Jörgen Sandberg in the competency area. This research was performed with twelve young entrepreneurs who participated in a pre-incubation program at a university located in the state of São Paulo. The data was collected based on two rounds of phenomenographic interviews held at the start and end of the program. Minutes from meetings between the students and the program advisors and with consultants from the junior company connected with the university were also used. The data was analyzed using phenomenographic techniques and the results point to the existence of three different ways of conceiving of enterprise within the group: (1) As an extension of a profession; (2) As an economic activity; (3) As an economic activity with a social impact. The evidence shows that these ways of experiencing enterprise lead to different strategies for learning and competency development. The evidence also shows that the individuals who had the deeper conceptions (2 and 3) developed their competency on more complex levels and obtained more success on the program, having their business projects evaluated and being invited to the incubation stage. After they participated in the program, their conceptions remained the same, which shows that learning occurred within the conception the individuals already possessed when they entered the program. This evidence helps to look at competency development in a new light. In order to develop professional competency it is necessary to go beyond the transmission of content required for good professional performance. It is fundamental to promote interventions that transform the conceptions individuals have of their activities. Individuals with deeper conceptions develop competencies on deeper levels.